THE EFFECT OF BUSINESS STRATEGY, COMPANY SIZE, AND SALES GROWTH ON FINANCIAL DISTRESS - Siti Hailatul Fikriyah; Rahma Wiyanti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to analyze the influence of business strategy, company size, and sales growth on financial distress in infrastructure sector companies listed on the Indonesia Stock Exchange for the 2020–2024 period. Financial distress is measured using the Altman Z-Score model as an indicator of a company's potential financial distress. This study uses a quantitative approach with secondary data obtained from company financial reports through a purposive sampling technique, resulting in 235 observational data. The analytical method used is panel data regression with the help of the EViews 14 application. Based on the results of model selection through the Chow test, the Hausman test, and the Lagrange Multiplier test, the best model used is the Fixed Effect Model (FEM). The results show that simultaneously, business strategy, company size, and sales growth have a significant effect on financial distress. Partially, business strategy and company size have a significant effect on financial distress, while sales growth does not have a significant effect on financial distress. These results indicate that the right business strategy and large company size can reduce the risk of financial distress, while sales growth does not necessarily reflect a healthy financial condition. This research is expected to provide theoretical contributions to the development of accounting and financial management literature and provide practical considerations for company management in managing financial risk sustainably.